FRACTURE CHARACTERISTICS ANALYSIS FOR NATURALLY FRACTURED RESERVOIR (NFR) ANALOGUE IN GRANITIC ROCKS AT MUARO SILOKEK, WEST SUMATRA - Tri Koesmawardani, Wildan
Naturally fractured reservoir (NFR) is an object of oil and gas exploration that is developing and has been carried out by foreign and domestic companies in Indonesia. Especially in basement rocks which is generally crystalline rock originating from intrusive or extrusive igneous rocks or low to high degree metamorphic rocks. The exploration of basement rocks is necessary to know fracture characteristics such as orientation, fracture attributes, fracture density distribution and other controlling factors, namely lithology or mineral composition. Generally in modeling natural fracture reservoirs, especially granitic basement rocks, quartz mineral composition factors are always ruled out. Whereas the composition of quartz has a significant influence on the response to fracture density in fault damage zone.